The concept of Ordnungspolitik: rule-based economic policymaking from the perspective of the Freiburg School - Jan Schnellenbach (Public Choice, 2021)
Should economic policy be guided by rules? In this paper, we take the perspective of the Freiburg School and trace its argument for rule-based Ordnungspolitik back to the roots of the concept. In doing so, will not offer a comprehensive review of the literature, but argue closely along the works of Walter Eucken, whose contributions are central to understanding the founding generation of the Freiburg School. We argue that not having rules is costly and therefore that the main thrust of the Freiburg approach remains valid. Good empirical arguments can be found for pursuing a rule-based Ordnungspolitik in order to avoid the costs of discretionary policymaking. Furthermore, we argue that reliance on stable rules does not incapacitate democratic decision-making. Rules rely on democratic support, and rule-based Ordnungspolitik also leaves substantial material scope for discretionary democratic decision-making.
Keywords: B15; B25; B41; H11; P48; P50; 330; Ordnungspolitik; Freiburg school; Economic orders; Economic constitutions